Measuring Business Administration College students’ ATTITUDES towards Blended Learning in KSA - Althuwaini, Sulaiman Abdullah (Journal of Economic, Administrative and Legal Sciences, 2020)
The Arab Open University (AOU) (is) among the first universities in the region to offer blended learning with the partnership of Open University in the United Kingdom (UK). Blended learning (BL) was initially seen to offer means for potential students to engage in distance learning education were pursuing their study was difficult or impossible in the mainstream education system. The purpose of this research was to measure students’ attitudes towards BL approach presented by AOU in Saudi Arabia. This research applied quantitative research design and a survey questionnaire was used to collect data from Business Administration College students in the academic year 2018-2019. Data were analyzed using (SPSS) where means, frequencies, standard deviation, t-test and one way ANOVA were applied and thus answered the research main questions. The study results revealed that the students’ overall attitudes towards BL are positive. Results also showed that there was statistically significant difference at (α =0.05) in the attitudes of students due to gender and profession. The study implications might be of interest to educationists in general and AOU in particular for planning and implementing future BL strategies. Certain practical recommendations are provided with hoping to enhance the open education system through improved learning and teaching strategies.